Cerebral Subdural Hematoma Following Spinal Anesthesia: Report of Two Cases - Mehrdad Moradi; Shoaleh Shami; Fariba Farhadifar; Karim Nesseri (Case Reports in Medicine)
Postdural puncture headache and cerebral subdural hematoma are among complications of spinal anesthesia with some common characteristics; however misdiagnosis of these two could result in a catastrophic outcome or prevent unwanted results by urgent interventions. With the purpose of increasing awareness of such complications and a speedy diagnosis, we report two cases of postspinal anesthesia headache that was timely diagnosed as cerebral subdural hematoma and prevented the likelihood of a disastrous outcome.